CSU Channel Islands: Writing & Multiliteracy Center John Spoor Broome Library Self-Study for Program Review (2020)
The Writing & Multiliteracy Center (WMC)'s mission is to provide students and faculty with a range of support services and programs that help them address 21st Century challenges of creatively thinking about, reading, and composing in written, oral, visual, multimodal, and digital forms of communications. We aim to foster a robust culture of writing and communication at CI, with an interest in helping students across disciplines learn modes of representation and communication that shape their academic, working, civic, and private lives.